Personas atzīšana par rīcībnespējīgu un ar to saistītās problēmas - Kuzņecova, Anna (Latvijas Universitāte, 2011)
Maģistra darba temats ir „Personas atzīšana par rīcībnespējīgu un ar to saistītās aktuālās problēmas”. Latvijā attiecībā uz minēto jautājumu ir lielas neskaidrības gan no materiālo, gan no procesuālo tiesību normu viedokļa. Atsevišķajos gadījumos personas nepamatoti tiek atzītas par rīcībnespējīgām un šādas situācijas demokrātiskā valstī nav pieļaujamās. Darba mērķis ir noskaidrot rīcībspējas un rīcībnespējas būtību, personas atzīšanas par rīcībnespējīgu un personas atzīšanas par rīcībspējīgu procesu, apzināt problēmas un trūkumus pašreizējā normatīvajā regulējumā, un sniegt to iespējamos risinājumus. Praksē pastāvošo problēmu attiecībā uz izskatāmo procesu pastāvēšana apdraud personas nepamatotu atzīšanu par rīcībnespējīgu, kas noved un var novest pie cilvēktiesību pārkāpumiem.

The Master’s Paper ‘The Process of Recognition of a Person as Lacking Capacity to Act and Related Issues’ has been worked out by a student of the Faculty of Law of the Latvia University Anna Kuzņecova. The Master’s Paper deals with the clarification of practical problems of the procedure which takes place when a person is recognised incapable to act and its aim is to find out what the basis for totally denying capacity to act is and whether all legal requirement have been observed as well as to determine the current problems and give the possible solutions. The author makes a conclusion that, first of all, the applicants and the society have no understanding of the meaning of incapacity to act and its consequences; that is why baseless applications are often submitted to court. Secondly, in case when a person partially lacks mental ability there should be determined a partial incapacity however the existing legal regulation does not allow it and provides no effective and adequate protection of the rights of an individual. Thirdly, the author detected that several uncertain questions related to forensic examination exist. In this connection the author considers that in order to appoint a forensic examination the court should have evidence that points to a possible incapacity to act. In a similar way the court judgements are based on conclusions contained in the forensic expert decisions taking no notice of other proofs. Another problematic question refers to the persons who may apply to court in order to recognise a person incapable or capacitated. From the practical point of view the global problem in this sphere is related to the participation in the procedure of those persons whose mental condition under question. Also the existing legal regulation does not allow the restoration of capacity to act in proportion to the needs and wishes of the person who was incapacitated due to a mental illness. The above mentioned problems cause risk of a person being recognised incapable without reason, thus their human rights can be substantially violated. Taking into account the above mentioned the author discusses some imprecise aspects of the procedure and its regulation and points out to the confrontation of opinions about this question both in theory and practice as well as mentions the necessity of implementation of the amendments to the corresponding legal acts. The Master’s Paper may be used as an informative material and as a basis for possible changes in the normative acts in the field of the researched issues. The Paper can also be useful for the formation of the understanding of the problem under examination and its possible solutions.
The Process of Recognition of a Person as Lacking Capacity to Act and Related Issues’
Keywords: Juridiskā zinātne